Development of Risk Assessment and Expert Systems for Cut Slopes - Omar, Husaini (2002)
Slope Assessment System (SAS) was developed to evaluate the risk of the cut slopes that will be used for slope monitoring, management and maintenance. The system was developed through consultations with field experts and field studies. The purposes of the consultations were to identify risk parameters. The risk rating was determined through field studies and then assigned to every parameters. Based on the field results, the risk hazard value (G-Rating) was proposed. The discontinuity data were analysed using stereographical method for Potential Instability (PI) Statement. By combining the PI Statement and G-Rating, the Slope Evaluation Statement (SES) was developed. The SES was divided into four categories: No Risk, Low Risk, Medium Risk and High Risk. To complete the evaluation process for SAS, suggestions were made for each category. The SAS was then transferred into a computer system which is the DSlope. The D-Slope is an expert system (ES) application to evaluate the cut slope conditions. The field data was stored in a database which can be updated and referred to through the ES. The possible roles for D-Slope are as an assessor and a peer system for cut slopes assessment.